Unique Adsorption Properties of Malachite Green on Interlayer Space of Cu-Al and Cu-Al-SiW12O40 Layered Double Hydroxides - Neza Rahayu Palapa; Novie Juleanti; Normah Normah; Tarmizi Taher; Aldes Lesbani (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Cu-Al layered double hydroxide (LDH) was intercalated with Keggin ion of polyoxometalate           K4[a-SiW12O40] to form Cu-Al-SiW12O40 LDH. The obtained materials were analyzed by X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR) spectroscopy, and Brunaur-Emmett-Teller (BET) surface area analysis. Furthermore, the materials were used as adsorbents of malachite green from aqueous solution. Some variables for adsorption, such as: effect of adsorption times, malachite green concentration, and also adsorption temperature, were explored. The results showed that diffraction at 11.72° on Cu-Al LDH has interlayer distance of 7.56 Å. The intercalation of that LDH with [a-SiW12O40]4− ion resulted increasing interlayer distance to 12.10 Å. The surface area of material was also increased after intercalation from 46.2 m2/g to 89.02 m2/g. The adsorption of malachite green on Cu-Al and          Cu-Al-SiW12O40 LDHs followed pseudo second order kinetic and isotherm Langmuir model with adsorption capacity of Cu-Al and Cu-Al-SiW12O40 LDHs was 55.866 mg/g and 149.253 mg/g, respectively. That adsorption capacity is equal with increasing interlayer space and surface area properties of material after intercalation. Thus, the adsorption of malachite green on Cu-Al and Cu-Al-SiW12O40 LDHs is unique and dominantly occurred on interlayer space of LDH as active site adsorption. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).